Application of Message Security Application Using Vigenere Cipher Algorithm Utilizing One Time Pad (OTP) Algorithm as a Key Generator - Pardede, A M H; Br Sitepu, Lorena Perbina; Zarlis, Muhammad; Tulus; Iskandar, Akbar; Sriadhi, S; Manurung, Rosida Tiurma; Siregar, Nurintan Asyiah; Sari, Ayu Esteka; Yunawati, Sri; Mursyidah, M; Mursalin, M; et al. (Journal of physics. Conference series, 2019)
Cryptography is the science and art of maintaining the security of messages when messages are sent from one place to another. One of the ways securing the form of text message information is by the encryption process using the Vigenere Cipher algorithm and utilizing the One Time Pad (OTP) algorithm as a key generator, where the message will be random when it is opened. The message encryption process used the vigenere cipher algorithm while OTP is used to secure the key with the same formula. After this research has been done, an application was designed to secure text messages by converting the text message into a random message so that the message was unreadable due to a secret message that could not be known by others. The results achieved can secure an encrypted message that cannot be reopened and if those messages were reopened, they must be decrypted.